Themes In The Song Lyrics Bandaids Mini Album By Keshi And Its Contribution To Poetry Teaching - Khuzaimatus Sa’adah; Indri Kustantinah; Nur Hidayat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Theme is a fundamental idea that unifies a tale, song, or literary work, making it simple to comprehend and enjoy. The theme serves as a concept, element, descriptor, and attribute. A song without a theme will be dry, unclear, and unlived. This research is aimed to (1) find out the main themes Keshi tries to show through his songs in Bandaids mini album; (2) find out the kinds of themes in Bandaids mini album by Keshi; (3) explain how the song lyrics in Bandaids mini album contribute to poetry teaching. This research using characters, plots, and setting as part of the intrinsic approach. Reads the song lyrics, listen the song, understand the lyrics, taking notes, conducting a thorough analysis, and organizing the data are the methods and approaches to collect data or can be called documentation and observation data collection. Gill’s theory used to discuss the main themes and kinds of themes in the song lyrics; the approach and method of data analysis used are descriptive qualitative with secondary data and three stream (1) data reduction; (2) data display; (3) drawing conclusion. In Gill’s theory (1995), the researcher used three ways to identify main themes, there are the title was selected by the writer of the song to convey a key message to the audience about the music; the characters' interests in moral and psychological development are reflected in how they develop, alter, and come to their own conclusions; repeating symbol or one that is employed at a crucial period might communicate a song's major topic. The result of the data showed 5 are indicated as the main themes and 5 are indicated as kinds of themes, namely love; heartbreak; depression; sadness; loneliness.